2013
DOI: 10.1111/jnc.12115
|View full text |Cite
|
Sign up to set email alerts
|

Profiling two indole‐2‐carboxamides for allosteric modulation of the CB1 receptor

Abstract: Allosteric modulation of G-protein coupled receptors (GPCRs) represents a novel approach for fine-tuning GPCR functions. The cannabinoid CB1 receptor, a GPCR associated with the CNS, has been implicated in the treatment of drug addiction, pain, and appetite disorders. We report here the synthesis and pharmacological characterization of two indole-2-carboxamides: 5-chloro-3-ethyl-1-methyl-N-(4-(piperidin-1-yl)phenethyl)-1H-indole-2-carboxamide (ICAM-a) and 5-chloro-3-pentyl-N-(4-(piperidin-1-yl)phenethyl)-1H-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
73
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(77 citation statements)
references
References 12 publications
4
73
0
Order By: Relevance
“…These, and other allosteric modulators of the CB 1 receptor, have been characterized on the basis of their actions in radioligand-binding assays and other functional in vitro assays of CB 1 receptor signal transduction (Horswill et al, 2007;Navarro et al, 2009;Pamplona et al, 2012;Piscitelli et al, 2012;Ahn et al, 2013;Baillie et al, 2013). In vivo, the purported negative allosteric modulator, PSNCBAM-1, reduced food intake (Horswill et al, 2007), an action consistent with CB 1 orthosteric antagonism (Di Marzo et al, 2001), although CB 1 receptor mediation of this anorectic effect was not ascertained.…”
Section: Introductionmentioning
confidence: 99%
“…These, and other allosteric modulators of the CB 1 receptor, have been characterized on the basis of their actions in radioligand-binding assays and other functional in vitro assays of CB 1 receptor signal transduction (Horswill et al, 2007;Navarro et al, 2009;Pamplona et al, 2012;Piscitelli et al, 2012;Ahn et al, 2013;Baillie et al, 2013). In vivo, the purported negative allosteric modulator, PSNCBAM-1, reduced food intake (Horswill et al, 2007), an action consistent with CB 1 orthosteric antagonism (Di Marzo et al, 2001), although CB 1 receptor mediation of this anorectic effect was not ascertained.…”
Section: Introductionmentioning
confidence: 99%
“…25 Subsequent work found that longer alkyl side chains with up to 9 carbon units at the C3 position of indole ring A could retain activity, whereas linkers other than an ethylene between the amide bond and the phenyl ring B resulted in total loss of activity. 26-28 In an attempt to expand our understanding of the structure-activity relationship on this scaffold, we have designed additional analogs by (i) exploring different substituents at the 4-, 3-, 2-positions of the phenyl ring B, (ii) examining several rigid cyclic ring linkers between the phenyl and the indole rings, and (iii) investigating the effects of shorter alkyl side chain at the C3 position and halogenations at the C5 position of the indole ring A. Here, we report the synthesis of these 1H-indole-2-carboxamide analogs and the evaluation of CB1 and CB2 activities in fluorometric imaging plate reader (FLIPR) based calcium mobilization assays.…”
Section: Introductionmentioning
confidence: 99%
“…7–9 , Figure 2) reported previously [3133]. Compounds 7 [31], 8 [33] and 9 [32, 35] have been demonstrated to have either comparable or improved allosteric effects to 1 [3133]. Therefore, they were selected along with 1 as the parent compounds to introduce photoactivatable functionalities.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, depending on the signaling pathways under investigation, compound 1 can behave either as a positive CB1 allosteric modulator [29] or a negative allosteric modulator [10, 30]. Following the discovery of 1 , several improved CB1 allosteric modulators have been identified from optimization of the indole-2-carboxamide scaffold [3135]. However, the investigation of the precise location and the structure of their binding sites is still in its early stage [3638].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation